Mismatch repair deficiency drives durable complete remission by targeting programmed death receptor 1 in a metastatic luminal breast cancer patient - Fremd, Carlo; Zapatka, Marc; Halama, Niels; Fejzibegovic, Nino; Lichter, Peter; Schirmacher, Peter; Kloor, Matthias; Marmé, Frederik; Schütz, Florian; Sinn, Peter; Jäger, Dirk; Schneeweiss, Andreas (Breast care, 2019)
Background: In the field of breast cancer tumor biology, triple-negative breast cancer patients are the main focus of current clinical trials exploring the use of immune checkpoint inhibitors due to higher frequencies of somatic mutations, neoantigens, and resulting tumor-specific T-cell reactivity. Case Report: Here, we present the case of a 66-year-old woman with metastatic luminal breast cancer that rapidly responded to monotherapy with pembrolizumab, a monoclonal anti-PD-1 antibody. This patient obtained a partial clinical response within the first cycle of treatment and an ongoing durable complete remission after 12 weeks. Except for a transient immune-related thyreoiditis, there were no side effects observed offering remarkable quality of life to the patient. To evaluate the underlying mechanisms, we performed immunohistochemistry, explored the mutational landscape by whole-exome sequencing, and identified potential T-cell epitopes by prediction of neoantigens with high affinity binding to one of the patient's HLA. Briefly, we found a strong infiltration of CD8+ T cells without staining for PD-L1 in the tumor stroma. Exome sequencing revealed an enormous frequency of somatic and tumor-specific alterations, mainly C>T/G>A transitions. The mutational pattern was further linked to genome instability and deficient mismatch repair supported by the loss of MSH6 protein expression and therefore leading to susceptibility to immune checkpoint blockade. Conclusion: Within the overall goal to establish operating procedures for breast cancer immunotherapy, we propose to re-evaluate testing for deficient mismatch repair and to further intensify the search for biomarkers predictive for the success of immune checkpoint modulation including all tumor biologic subtypes of breast cancer.
Gesehen am 22.05.2019